The Mediating Role of Autotelic Personality in the Relationship Between Motivation Regulation and Flow Experiences in Adults - ÜMMET, DURMUŞ (DERGIPARK AKAD, 2021)
This research aims to examine the role of autotelic personality traits in the relationship between motivational regulating skills and the flow experience of adult individuals. The research is structured in a correlational model. The sample of the study consists of 535 adult individuals selected with the convenience sampling method. Of the individuals in the sample group, 368 (68.8%) are female, 167 (31.2%) are male, and the average age is 34.89. The Flow Experience Scale, Autotelic Personality Inventory, and Motivation Regulation Scale were used as data collection tools in the research. Pearson Product Moment Correlation, Conditional Process Analysis, and Bootstrapping analysis were used to analyze the data to test the research aims. As a result of the analysis, positive and significant relationships between flow experience, autotelic personality, and motivational regulation were determined. According to the established model, it has been concluded that autotelic personality traits have a full mediator role in the relationship between motivation regulation skills and flow experience in adult individuals. This result shows that the significant effect of motivation regulation on flow experience disappears with the inclusion of autotelic personality traits in the model; in other words, the effect of autotelic personality traits on flow experience is greater than motivation regulation.
Keywords: Flow experience; autotelic personality; motivation regulation; intermediary model; MODERATOR; STUDENTS